IMMUNOSTIMULATORY EFFECT OF METHANOLIC LEAVES EXTRACT OF PSIDIUM GUAJAVA (GUAVA) ON HUMORAL AND CELL-MEDIATED IMMUNITY IN MICE - A. Shabbir; H. I. Butt; M. Shahzad; H. M. Arshad; I. Waheed (Journal of Animal and Plant Sciences, 2016)
Psidium guajava (Guava) has been used in the traditional system of medicine to treat various inflammatory diseases. The present study investigates the immunomodulatory effect of methanolic extract of Guava leaves on humoral and cell-mediated immunity. Delayed type hypersensitivity (DTH) and cyclophosphamide-induced myelo-suppression assays were performed to evaluate the effect of Guava leaves extract on cell-mediated immunity. Haemagglutination assay and mice lethality test were conducted to evaluate the effects of Guava leaves extract on humoral immunity. A total of 36 mice were divided into six groups and each group comprised of six mice. Low, medium, and high dose groups received 100, 150, and 200 mg/kg b.w., intraperitoneal doses of Guava leaves extract, respectively.The treatment with Guava extract showed significant increase in the counts of WBC, RBC, platelet, monocyte, neutrophil, eosinophil, lymphocyte, and level of hemoglobin as compared with control group. Guava extract significantly prevented the cyclophosphamide-induced myelosuppression and increased the DTH after 24 h, 48 h and 72 h. The treatment with Guava extract caused significant increase in anti-SRBCs antibody titer and reduced the mice lethality ratio as compared with cyclophosphamide. In conclusion, current study suggests that Guava leaves extract can stimulate both humoral and cell-mediated immunity in mice.
Keywords: Immunomodulation; Psidium guajava; Humoral immunity; Cell-mediated immunity